A new species of the genus Sason (Araneae: Barychelidae) from Rameshwaram Island, Tamil Nadu, India - Siliwal, Manju; Molur, Sanjay (Zootaxa, 2009)
A new species of the genus Sason, S. rameshwaram sp. nov., of the Brush-footed trapdoor spider family Barychelidae is described from Rameshwaram Island, Tamil Nadu, India. Nest structure and habitat are documented.